Predominantly Eastward Long-Distance Dispersal in Pantropical Ochnaceae Inferred From Ancestral Range Estimation and Phylogenomics - Schneider, Julio V.; Jungcurt, Tanja; Cardoso, Domingos; Amorim, André M.; Paule, Juraj; Zizka, Georg (Frontiers in Ecology and Evolution, 2022)
Ochnaceae is a pantropical family with multiple transoceanic disjunctions at deep and shallow levels. Earlier attempts to unravel the processes that led to the actual biogeographic patterns suffered from insufficient phylogenetic resolution and unclear delimitation of some of the genera. In the present study, we estimated divergence time and ancestral ranges based on a phylogenomic framework with a well resolved phylogenetic backbone to tackle issues of the timing and direction of dispersal that may explain the modern distribution of Ochnaceae. The nuclear data provided the more robust framework for divergence time estimation compared to the plastome-scale data, although differences in the inferred clade ages were mostly small. While Ochnaceae most likely originated in West Gondwana during the Late Cretaceous, all crown-group disjunctions are inferred as dispersal-based, most of them as transoceanic long-distance dispersal during the Cenozoic. All long-distance dispersals occurred in an eastward direction except for the SE Asian clade of Sauvagesieae, which was founded by trans-Pacific dispersal from South America. The by far most species-rich clade, Ochninae, originated from a widespread neotropical-African ancestor or in the Neotropics and dispersed to Africa with subsequent radiation and dispersal to the Malagasy region and tropical Asia on multiple instances in three genera during the Miocene-Pliocene. Especially Ochna might have used the South Arabian land corridor to reach South Asia. Thus, the pantropical distribution of Ochnaceae is the result of long-distance dispersal either transoceanic or via land bridges/corridors, whereas vicariance might have played a role only along the stem of the family.